Informasi Dengan Minat Siswa SMP Dalam Memilih Jurusan Kuliner di SMK - Yolanda, Ratifah; Elida, Elida; Gusnita, Wiwik; Yasih, Fitri (SENTRI: Jurnal Riset Ilmiah, 2025)
Vocational education, particularly Vocational High Schools (SMK), plays an important role in preparing graduates who are ready to work or continue their studies. However, the Culinary Arts program at SMK Negeri 2 Gunung Talang still faces low student enrollment. This study aimed to examine the relationship between vocational school information and junior high school students’ interest in choosing the culinary expertise program. Using a quantitative correlational design, the population consisted of 869 ninth-grade students in Gunung Talang District, with 274 students selected through proportional stratified random sampling. The research instrument was a Likert-scale questionnaire tested for validity and reliability (α = 0.627 for information; α = 1.000 for interest). Results showed that the average score of vocational school information was 82.80 (SD = 9.629), categorized as fairly good, with the highest indicator being facilities and infrastructure (mean = 2.86) and the lowest being sources of information (mean = 2.60). Students’ interest scored an average of 95.80 (SD = 13.528), also fairly good, with the highest indicators on personality (mean = 2.89) and socio-cultural environment (mean = 2.87). Pearson correlation analysis revealed a strong and significant positive relationship (r = 0.678; p = 0.000) between vocational school information and students’ interest. These findings highlight the importance of quality and accessible information in shaping students’ interest, emphasizing the need for schools to optimize information dissemination strategies to strengthen the attractiveness of the culinary program.